Effect of a training program on the psychological, cultural, and social alienation experienced by foreign students in Jordan - Al-Habies, Feras; Al-Kernawi, Alean; Al-Ja'afreh, Somaya Abdel-Hameed; Alwani, Wafa Ali Mahmoud; Alorani, Omar Ismail Hamzeh; Al-Jaloudi, Diya Ahmad; Khawaldeh, Omar Abdallah (Journal of International Students, 2025)
In this study, we examined the effectiveness of an educational training program in reducing psychological, cultural, and social alienation among international students. A total of 73 undergraduate students from diverse nationalities participated in the study. The training program comprised six seminars delivered over three weeks, with two lectures conducted weekly. Topics covered included Jordanian culture and traditions, academic procedures, students’ rights and responsibilities, support services, local geography, financial management, and safety. Pre- and post-program assessments utilized validated tools to measure levels of alienation. Findings revealed a significant reduction in social and cultural alienation, underscoring the program’s success in fostering social connections and cultural understanding. However, an unexpected increase in psychological alienation was noted, highlighting the need to address psychological challenges more effectively. These results emphasize the importance of comprehensive orientation programs tailored to mitigate all dimensions of alienation, ultimately enhancing the overall well-being of international students.